STATE-OWNED BANK AND NATIONAL PRIVATE FOREIGN EXCHANGE COMMERCIAL BANK FINANCIAL PERFORMANCE: BEFORE AND DURING THE COVID-19 PANDEMIC ERA - Nurul Azizah Az zakiyyah; Firsty Ramadhona Amalia Lubis (Universitas Tidar, 2022)
The banking sector has a fairly important role related to its function which is a sub-system in the economy of a country. In the modern era, the banking sector is used in various activities including the provision of goods and services, consumption, and investment made by the community. This study aims to determine the performance of commercial banks before and during the COVID-19 pandemic. The data used in this study is cross-section data from 28 state-owned banks and National Private Foreign Exchange Commercial Bank in 2019 and 2020. The data were analyzed using the CAMEL analysis method. The result of the analysis showed there is no significant difference in performance between state-owned banks and National Private Foreign Exchange Commercial Bank before and during the covid-19 pandemic.